PENGARUH KINERJA KEUANGAN DAN TATA KELOLA ORGANISASI TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORTING - Muhammad Williams Rahaditama (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the influence of determinants of sustainability reporting (empirical study on participating companies in the Asia Sustainability Reporting Rating (ASRRAT)). Determinants of sustainability reporting are classified into 2, namely: financial performance and corporate governance. Financial performance includes: company size, profitability, and leverage. Corporate governance includes: board of directors and audit committee. The data used in this study are secondary data in the form of sustainability report data, annual reports and financial statements of companies listed on the Asia Sustainability Reporting Rating (ASRRAT) in 2018-2020 with sample selection using purposive sampling method. This study uses a quantitative approach with analytical methods using multiple linear regression test. The results of the study show that firm size, profitability, and leverage have no effect on the sustainability reporting disclosure. Meanwhile, the board of directors and the audit committee affect the sustainability reporting disclosure.